1997
DOI: 10.1136/fn.77.1.f47
|View full text |Cite
|
Sign up to set email alerts
|

Long term hepatitis B vaccine in infants born to hepatitis B e antigen positive mothers

Abstract: Hepatitis B virus (HBV) is a ubiquitous organism that leads to a wide range of liver diseases which often result in chronic or fatal outcomes. It has been estimated that there are about 400 to 500 million HBV carriers in the world, and globally, each year more than a million deaths are attributed to the consequences of HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 18 publications
1
39
0
6
Order By: Relevance
“…1 To control HBV infection, universal neonatal immunisation with the hepatitis B vaccine was introduced more than 3 decades ago, and its efficacy has been reported in many studies that have shown not only a reduction in the prevalence of childhood HBV infection, but also the presence of an anamnestic response that could maintain immunoprotection for many years. [2][3][4][5][6][7][8][9][10][11][12][13][14] Indeed, in Taiwan, following introduction of the vaccine, the incidence of hepatocellular carcinoma (HCC) in children was reduced from 0.54 to 0.20 per 100,000 children aged 6-14 years in those born before versus after the vaccination program. 15 In Hong Kong, selective active-passive hepatitis B immunization was first administered to neonates born to mothers screened positive for hepatitis B surface antigen (HBsAg) from late 1983 to 1988, 16 followed by universal neonatal HBV vaccination from November 1988, 17 and the vaccine has become widely available since.…”
Section: Introductionmentioning
confidence: 99%
“…1 To control HBV infection, universal neonatal immunisation with the hepatitis B vaccine was introduced more than 3 decades ago, and its efficacy has been reported in many studies that have shown not only a reduction in the prevalence of childhood HBV infection, but also the presence of an anamnestic response that could maintain immunoprotection for many years. [2][3][4][5][6][7][8][9][10][11][12][13][14] Indeed, in Taiwan, following introduction of the vaccine, the incidence of hepatocellular carcinoma (HCC) in children was reduced from 0.54 to 0.20 per 100,000 children aged 6-14 years in those born before versus after the vaccination program. 15 In Hong Kong, selective active-passive hepatitis B immunization was first administered to neonates born to mothers screened positive for hepatitis B surface antigen (HBsAg) from late 1983 to 1988, 16 followed by universal neonatal HBV vaccination from November 1988, 17 and the vaccine has become widely available since.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the antibody after immunization will decrease with time, but immune memory will be present up to 13 years after the immunization, so children and adults with undetectable anti-HBs will still be protected from HBV infection. 10,[16][17][18][19] In this study, 18 children who had received both active and passive immunization at the age of less than 7 days were not infected by HBV. Six out of 25 children who only received active immunization at the age of more than 7 days were infected.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of prophylactic HBV immunization with or without HBIg had been evaluated in a longitudinal study. [17][18][19] Beasley reported that 80-95% of babies from positive HBsAg mothers who received HBV immunization and HBIg prophylaxis soon after birth were not infected by HBV. 19 Zamir reported that 89% of babies from negative HBeAg carrier mothers who only received active immunization soon after birth developed protective levels of anti-HBs.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study (11) a GMC of 3 341 mIU/mL was found one month after completion of an immunization schedule of 0, 1, 2, and 12 months. Among the neonates in the group who were not boosted at month 60 but were followed up to month 96 the seropositivity was still 95.5%.…”
Section: Discussionmentioning
confidence: 99%